Touching the Elephant: A Holistic Approach to Understanding International Student Experiences - Bista, Krishna (Journal of International Students, 2019)
In this editorial essay, the author uses the Indian parable known as The Blind Men and an Elephant to illustrate different perspectives that may frame the international student experience. It discusses the abundance of blinders and high stakes in a growth industry. The editorial illustrates the need to shift perspectives and widen the circle of support and why a holistic approach matters.